Plasmodium vivax vaccine: What is the best way to go? - Veiga, Gisele Tatiane Soares da; Moriggi, Matheus Ribeiro; Vettorazzi, Jean Franciesco; Müller-Santos, Marcelo; Albrecht, Letusa (Frontiers in Immunology, 2023)
Malaria is one of the most devastating human infectious diseases caused by Plasmodium spp. parasites. A search for an effective and safe vaccine is the main challenge for its eradication. Plasmodium vivax is the second most prevalent Plasmodium species and the most geographically distributed parasite and has been neglected for decades. This has a massive gap in knowledge and consequently in the development of vaccines. The most significant difficulties in obtaining a vaccine against P. vivax are the high genetic diversity and the extremely complex life cycle. Due to its complexity, studies have evaluated P. vivax antigens from different stages as potential targets for an effective vaccine. Therefore, the main vaccine candidates are grouped into preerythrocytic stage vaccines, blood-stage vaccines, and transmission-blocking vaccines. This review aims to support future investigations by presenting the main findings of vivax malaria vaccines to date. There are only a few P. vivax vaccines in clinical trials, and thus far, the best protective efficacy was a vaccine formulated with synthetic peptide from a circumsporozoite protein and Montanide ISA-51 as an adjuvant with 54.5% efficacy in a phase IIa study. In addition, the majority of P. vivax antigen candidates are polymorphic, induce strain-specific and heterogeneous immunity and provide only partial protection. Nevertheless, immunization with recombinant proteins and multiantigen vaccines have shown promising results and have emerged as excellent strategies. However, more studies are necessary to assess the ideal vaccine combination and test it in clinical trials. Developing a safe and effective vaccine against vivax malaria is essential for controlling and eliminating the disease. Therefore, it is necessary to determine what is already known to propose and identify new candidates.